1993
DOI: 10.1002/jnr.490350407
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular transport of myelin proteolipid and cerebroside sulfates to the myelin membrane

Abstract: The possibility that cerebroside sulfates and myelin proteolipid (PLP) could be simultaneously located in transport vesicles destined to be assembled in myelin was investigated in the brain of 20 day old rats. The brain was homogenized and fractionated according to Burkart et al. (J Biol Chem 257:3151-3156, 1982) to obtain a microsomal fraction that was further subfractionated in a linear sucrose density gradient following the procedure of Siegrist et al. (J Neurochem 33:497-504, 1979) to obtain a vesicular fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…This finding is rather surprising, given a reported role for GalC-enriched microdomains but not sulfatide in PLP transport to the myelin sheet (11). However, although it is controversial, sulfatide has been implicated in PLP transport (48,49). The apparently contradictory findings likely originate from the different experimental conditions, including, among others, the polarized status of the cells.…”
Section: Resultsmentioning
confidence: 94%
“…This finding is rather surprising, given a reported role for GalC-enriched microdomains but not sulfatide in PLP transport to the myelin sheet (11). However, although it is controversial, sulfatide has been implicated in PLP transport (48,49). The apparently contradictory findings likely originate from the different experimental conditions, including, among others, the polarized status of the cells.…”
Section: Resultsmentioning
confidence: 94%
“…Inhibition of the synthesis of glycosphingolipids has been reported to disrupt the transport of PLP to myelin membrane, leading to a suggestion that glycolipids (probably sulfatide) are coupled to the intracellular transport of PLP to the plasma membrane surface (Pasquini et al, 1989;Brown et al, 1993). Our present approach of analysis has allowed us to test this hypothesis more directly.…”
Section: Plp Transport To the Ol Plasma Membrane Proceeds In The Absementioning
confidence: 89%
“…It has been postulated that transport of proteolipid protein (PLP), the major myelin component in the CNS, is coupled to glycosphingolipid synthesis (Pasquini et al, 1989). Moreover, it was concluded that cotransport of PLP with sulfogalactosylceramide (sulfatide; Brown et al, 1993) occurs. However, Bansal and Pfeiffer (1994) have shown that inhibition of sulfatide synthesis does not prevent PLP accumulation in the OLG's processes.…”
Section: Discussionmentioning
confidence: 99%